2007
DOI: 10.1590/s0101-41612007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Interação universidade-empresa no Brasil: evidências do Diretório dos Grupos de Pesquisa do CNPq

Abstract: Resumo O presente trabalho investiga a interação universidade-empresa no Brasil por meio de informações disponíveis no Diretório dos Grupos de Pesquisa do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
92

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 31 publications
1
32
0
92
Order By: Relevance
“…In a recent research, Østergaard (2009) shows that, in 100 informal relations between company and university researchers, only 31 were of medium (24) or high (7) value of knowledge. This data support our and other authors (Cohen et al, 2002;Rapini, 2007) view that usually companies seek for technical knowledge at universities, instead of state-of-the-art knowledge.…”
Section: Area Of Science Number Of Companies Number Of Research Groupssupporting
confidence: 92%
See 2 more Smart Citations
“…In a recent research, Østergaard (2009) shows that, in 100 informal relations between company and university researchers, only 31 were of medium (24) or high (7) value of knowledge. This data support our and other authors (Cohen et al, 2002;Rapini, 2007) view that usually companies seek for technical knowledge at universities, instead of state-of-the-art knowledge.…”
Section: Area Of Science Number Of Companies Number Of Research Groupssupporting
confidence: 92%
“…iii) Knowledge flows from industry to university, where industry generates a request, based on marketing demands or internal P&D problems (Rapini, 2007;Yusuf, 2008). This indicator of flow is based on the following indicators of content:…”
Section: ! Figure 1 -Knowledge Flow Between the University And Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Além desses fatores, se sobressai no debate a dimensão locacional (proximidade geográfica) como elemento que condiciona a interação das universidades com as empresas, ao considerar que essa proximidade tem o potencial de facilitar colaborações informais e formais, contatos mais intensivos entre as partes e maior acesso à infra-estrutura de pesquisa detida pelas universidades por parte do tecido industrial da região em questão (Rapini, 2007).…”
Section: Notas Sobre a Relação Universidade-empresaunclassified
“…There seem to be missing linkages across organisations, as well as a limited translation of academic research into commercial or technological applications in countries like Brazil (MENEGHEL; GOMES, 2003;DAGNINO, 2004;RAPINI et al, 2009). As a result, previous investigations have suggested that interactions between university and industry (U-I) are weak and localised, that is, while some firms indeed benefit from their contacts with universities and public labs, for the most part there is little fruitful interaction -a finding that seems to hold among developing countries of Latin America, Africa and Asia (ETZKOWITZ; DE MELLO, 2003;ETZKOWITZ;DE MELLO;ALMEIDA, 2005;RAPINI, 2005;SCHILLER, 2006).…”
Section: Introductionmentioning
confidence: 99%